The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1177/014556130007901008
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Nasal gel for the Treatment of Common Cold Symptoms: A Double-blind, Placebo-controlled Trial

Abstract: Effective treatments fo r the common cold have been diffic ult to develop because so many different types of virus are respons ible for this condition. Oral zinc has been studied as a possible mea ns ofpreventing O I' alle viating symptotns, with mixed resu lts. We studied a new app roach to zinc therapy-an ever-the-cou nter nasal ge l formu lation (Zieam)-to independently eva luate its efficaey as a treatment fo r the common cold. Our study was conducted at [o ur sites ove r a 5-month pe riod. The study group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 12 publications
0
52
0
2
Order By: Relevance
“…Among the 7 studies reporting no effect, 3 fulfilled all 11 criteria [23][24][25], 1 met 8 criteria [14], 1 met 7 criteria [15], and 2 met 6 criteria [26,27]. Among the studies reporting positive effects, 1 met all 11 criteria [28], 2 met 10 criteria [29,30], 2 met 7 criteria [31,32], and 2 met 6 criteria [6,33]. Of the 4 studies that fulfilled all 11 criteria [23][24][25]28], 2 studies [23,25] reported that zinc lozenges have no effect on the symptom severity and duration of common cold, 1 study [24] reported no effect of zinc nasal spray, and 1 study [28] reported a positive effect of zinc nasal gel on the symptoms and duration of the common cold.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 7 studies reporting no effect, 3 fulfilled all 11 criteria [23][24][25], 1 met 8 criteria [14], 1 met 7 criteria [15], and 2 met 6 criteria [26,27]. Among the studies reporting positive effects, 1 met all 11 criteria [28], 2 met 10 criteria [29,30], 2 met 7 criteria [31,32], and 2 met 6 criteria [6,33]. Of the 4 studies that fulfilled all 11 criteria [23][24][25]28], 2 studies [23,25] reported that zinc lozenges have no effect on the symptom severity and duration of common cold, 1 study [24] reported no effect of zinc nasal spray, and 1 study [28] reported a positive effect of zinc nasal gel on the symptoms and duration of the common cold.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of 14 studies [6,14,15,26,27,29,31,32] did not show an intent-to-treat analysis of all subjects initially enrolled in the study. Seven studies [6,14,15,26,27,32,33] did not have a quantifiable hypothesis or sample size calculation. Proof of blinding was lacking in 7 studies [6,26,27,[30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations